NEW METHOD OF CONSERVATIVE TREATMENT OF CHRONIC RHINOSINUSITIS IN CHILDREN WITH CYSTIC FIBROSIS - S.G. Ushakova; P.I. Belavina; O.I. Simonova; O.V. Karneeva ("Paediatrician" Publishers LLC, 2010)
Development of new methods of treatment of cystic fibrosis (CF) is necessary because of severe clinical course of this disease and frequent development of rhinosinusitis in children. Rhinosinusitis in patients with CF has chronic clinical course, frequent exacerbation and it is hardly treated with traditional therapy. Authors studied effectiveness of treatment of chronic sinusitis with inhalations of dornase alfa in accessory sinuses of nose with compressor inhalator PARI LC SINUS. 23 children with severe clinical course of CF, chronic sinusitis and rhinitis remaining despite recommended treatment were observed during the study. Treatment with inhalations of dornase alfa with PARI LC SINUS had beneficial effect, and it can be recommended for inclusion in pediatric practice. Key words: children, cystic fibrosis, chronic rhinosinusitis, dornase alfa, PARI LC SINUS, conservative therapy.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):72-79)